Zn4 (BO3) 2 (CO2CH2NH2) 2. H2O compound and crystal, preparation method and application thereof
The Zn4(BO3)2(CO2CH2NH2)2·H2O compound was prepared by hydrothermal reaction, achieving coplanar uniform arrangement of (BO3)3-groups, solving the problem that it is difficult to obtain high-performance ultraviolet nonlinear optical crystals in the borate system, and the prepared crystals have excellent optical properties.
Patent Information
- Application Number
- CN202411830569.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-12
AI Technical Summary
In borate systems, it is difficult to efficiently obtain a coplanar and uniform arrangement of (BO3)3-groups, resulting in very few borates that can have large band gaps, frequency doubling coefficients and birefringence at the same time, limiting the performance of ultraviolet nonlinear optical crystals.
By mixing Zn-containing compounds, B-containing compounds and glycine-containing ligand compounds for hydrothermal reaction, Zn4(BO3)2(CO2CH2NH2)2·H2O compound is prepared. The crystal structure is alternately stacked by the [Zn2BO3ON]∞ layer containing (BO3)3- and the glycine organic layer to achieve coplanar and uniform arrangement of (BO3)3-groups.
The prepared Zn4(BO3)2(CO2CH2NH2)2·H2O crystal has a large band gap and frequency doubling coefficient, the ultraviolet absorption edge can reach 201nm, and the transmittance is high in the range of 240-1400nm, which is suitable for ultraviolet nonlinear optical applications.
Smart Images

Figure CN119823397A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional crystal materials, and in particular relates to a Zn4(BO3)2(CO2CH2NH2)2·H2O compound and its crystal, a preparation method and application in nonlinear optics. Background Art
[0002] Nonlinear optical (NLO) crystal materials are a new type of optoelectronic functional materials widely used in the field of laser technology. As the core device in all-solid-state lasers, they can easily convert mature lasers to other bands by relying on their frequency conversion function, so they can be widely used in cutting-edge scientific research, laser micromachining, secure communications, information storage, laser medical treatment, and national defense and military industries. Currently, the ultraviolet nonlinear optical crystals that have been commercialized are mainly concentrated in the borate system, including β-BaB2O4 (abbreviated as BBO), LiB3O5 (abbreviated as LBO), CsB3O5 (abbreviated as CBO) and CsLiB6O 10 (abbreviated as CLBO) etc. In the borate system, (BO3) 3- The planar triangular π-conjugated group has a wide band gap and a large microscopic second-order polarizability, and is one of the most excellent functional groups. Its coplanar arrangement is conducive to the construction of nonlinear optical crystals with large band gaps, frequency doubling coefficients, and birefringence. However, since B and O can also form (BO4) 5- The connection patterns between the groups are flexible and changeable, and it is often difficult to efficiently obtain the desired (BO3) 3- The groups are arranged in a coplanar structure. This is also the reason why, although there are many types of borates, very few borates can have a large band gap, frequency doubling coefficient and birefringence at the same time. Therefore, exploring new ultraviolet nonlinear optical crystals with excellent performance is still a very challenging task. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a compound with the chemical formula of Zn4(BO3)2(CO2CH2NH2)2·H2O.
[0004] The present invention also provides a method for preparing the compound having the chemical formula Zn4(BO3)2(CO2CH2NH2)2·H2O, the method comprising the following steps:
[0005] The compound containing Zn, the compound containing B and the compound containing glycine ligand are mixed and subjected to hydrothermal reaction to prepare the compound.
[0006] According to an embodiment of the present invention, the Zn-containing compound is selected from at least one of ZnO, Zn(OH)2, and ZnC4H8N2O4, preferably Zn(OH)2.
[0007] According to an embodiment of the present invention, the B-containing compound is selected from at least one of H3BO3, B2O3, and HBO2, preferably H3BO3.
[0008] According to an embodiment of the present invention, the glycine-containing ligand compound is selected from one of C3H4N2O2, C2H5NO2, and C2H7ClNO2, preferably C2H5NO2.
[0009] According to an embodiment of the present invention, the molar ratio of the Zn-containing compound, the B-containing compound, and the glycine ligand-containing compound is (1-3): (1-3): 1; preferably (1-2): (1-2): 1; exemplarily 1: 2: 1. For example, the molar ratio of Zn(OH)2: H3BO3: C2H5NO2 is (1-3): (1-3): 1.
[0010] According to an embodiment of the present invention, the hydrothermal reaction is carried out in a solvent, and the solvent can be selected from water or a mixed solvent of water and CF3COOH, for example, the volume ratio of water to CF3COOH is (3-20):1.
[0011] Preferably, the solvent is a mixture of 5-9 ml of water and 0.5-1.5 ml of CF3COOH, and exemplified by 9 ml of deionized water and 0.5 ml of CF3COOH.
[0012] According to an embodiment of the present invention, the reaction temperature of the hydrothermal reaction may be 160-200° C., preferably 180-200° C., for example 180° C. Further, the heating rate of the hydrothermal reaction may be 10-30° C. / h, exemplified by 10° C. / h, 20° C. / h, and 30° C. / h.
[0013] According to an embodiment of the present invention, the reaction time of the hydrothermal reaction may be 1 to 5 days, preferably 2 to 4 days, exemplified by 2, 3, or 4 days.
[0014] According to an embodiment of the present invention, the method further comprises: cooling the hydrothermal reaction product.
[0015] Preferably, after the reaction is completed, the temperature is lowered to room temperature at a rate of 1-10°C / h.
[0016] The present invention also provides a nonlinear optical crystal, the chemical formula of which is Zn4(BO3)2(CO2CH2NH2)2·H2O, that is, the nonlinear optical crystal is a Zn4(BO3)2(CO2CH2NH2)2·H2O crystal.
[0017] According to an embodiment of the present invention, the Zn4(BO3)2(CO2CH2NH2)2·H2O crystal belongs to the trigonal system, the space group is P3221, and the unit cell parameters are α=β=90°, γ=120°, z=6.
[0018] According to an embodiment of the present invention, the nonlinear optical crystal has substantially the following Figure 2 X-ray diffraction pattern shown.
[0019] According to an embodiment of the present invention, the powder frequency doubling effect of the nonlinear optical crystal is about 0.85 times that of KH2PO4 (KDP).
[0020] According to the embodiment of the present invention, the ultraviolet absorption edge of the nonlinear optical crystal can reach 201nm, the band gap of the crystal can be as wide as 6.17eV, and a higher transmittance can be achieved between 240 and 1400nm. That is, the nonlinear optical crystal is an ultraviolet optical crystal.
[0021] According to an embodiment of the present invention, the nonlinear optical crystal structure is composed of a honeycomb [Zn2BO3ON] ∞ Layers and glycine organic layers are stacked alternately.
[0022] The present invention also provides a method for preparing the nonlinear optical crystal, which comprises: mixing a Zn-containing compound, a B-containing compound, a glycine ligand-containing compound and a solvent, and heating and crystallizing the mixture to obtain the crystal.
[0023] Preferably, the selection of the Zn-containing compound, the B-containing compound, the glycine ligand-containing compound and the solvent are respectively consistent with the selection in the preparation method of the compound with the chemical formula Zn4(BO3)2(CO2CH2NH2)2·H2O.
[0024] According to an embodiment of the present invention, the temperature of the heating crystallization is 160 to 200°C;
[0025] The heating crystallization time is 3 to 10 days, preferably 3 to 7 days, and exemplarily 5, 6, or 7 days.
[0026] Preferably, the preparation method further comprises: after the crystallization is completed, cooling, separating and drying the reaction liquid to obtain the crystals.
[0027] Preferably, during the cooling process, the cooling rate is 1-10°C / h, exemplified by 1°C / h, 5°C / h, and 9°C / h.
[0028] According to an embodiment of the present invention, the method for preparing the crystal specifically comprises the following steps:
[0029] (a) mixing a Zn-containing compound, a B-containing compound, a glycine ligand-containing compound and a solvent in a certain proportion, heating the mixture to 160 to 200° C. at a rate of 10 to 30° C. / hour, and crystallizing the mixture at a constant temperature for 3 to 10 days;
[0030] (b) After the crystallization is completed, the reaction system is cooled to room temperature at a rate of 1 to 10° C. / h, and the crystals can be obtained after separation and drying.
[0031] The present invention also provides the above crystal in the fields of laser frequency doubling, electro-optic modulation, photorefractive information processing and information storage, catalysis, etc.; preferably, it is used in a frequency doubling device in an all-solid-state laser.
[0032] Beneficial effects of the present invention:
[0033] The inventors found that in the borate system, the π-conjugated (BO3) 3- The planar triangular groups have a wider band gap and a larger microscopic second-order polarizability, and their coplanar arrangement is conducive to the synthesis of nonlinear optical crystals with large band gaps and frequency doubling coefficients. (BO3) 3- The group is considered to be the most excellent nonlinear optically active group in borates, and the most representative crystal is KBe2BO3F2 (KBBF). The KBBF structure is a typical layered structure, and the weak interlayer force is the root cause of its severe layered growth habit. Structural modification based on the KBBF structure, including enhancing the interlayer force, is a hot spot for creating new nonlinear optical crystals. The present invention creatively uses glycine as a connecting group to construct an organic-inorganic hybrid ultraviolet nonlinear optical crystal with KBBF structural characteristics.
[0034] (1) The present invention provides a novel glycine-boric acid composite Zn4(BO3)2(CO2CH2NH2)2·H2O compound and its crystal, the crystal has a structural configuration similar to KBBF, and its crystal structure is composed of (BO3) 3- [Zn2BO3ON] ∞ Layers and glycine organic layers are stacked alternately; [Zn2BO3ON] ∞ Layer and [Be2BO3F2] in KBe2BO3F2(KBBF) structure ∞ The layers are very similar, within the layer (BO3) 3- The groups are arranged almost identically, contributing to the main nonlinear effect of the crystal. What is special is that this structure realizes [Zn2BO3ON] for the first time through the glycine group. ∞ The crystal has the potential to be used in the ultraviolet region; at the same time, the crystal does not absorb moisture and has good physical properties.
[0035] (2) The Zn4(BO3)2(CO2CH2NH2)2·H2O crystal of the present invention outputs a strong 532nm light (i.e., double frequency) under 1064nm laser irradiation, and its powder double frequency effect is about 0.85 times that of KH2PO4 (KDP), and phase matching can be achieved.
[0036] (3) The Zn4(BO3)2(CO2CH2NH2)2·H2O crystal of the present invention has a wide light transmittance range, has a high transmittance between 240-1400nm, an ultraviolet cutoff edge that can reach 201nm, and a band gap as wide as 6.17eV. It can be used in the ultraviolet region and has potential application prospects in the fields of nonlinear optics, laser technology, electro-optic modulation, photorefractive information processing and information storage, and catalysis.
[0037] (4) The physical and chemical properties of the Zn4(BO3)2(CO2CH2NH2)2·H2O crystal of the present invention are stable.
[0038] (5) The preparation method of the Zn4(BO3)2(CO2CH2NH2)2·H2O compound and crystal of the present invention has a simple process, a fast growth rate and a low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a schematic diagram of the crystal structure of the Zn4(BO3)2(CO2CH2NH2)2·H2O crystal of the present invention.
[0040] Figure 2 This is a comparison chart of the X-ray diffraction simulation spectrum obtained by fitting the crystal structure of the sample in Example 2 according to the single crystal X-ray diffraction data and the sample powder X-ray diffraction obtained in Example 2.
[0041] Figure 3 This is the UV-visible-near infrared transmission spectrum of the sample in Example 2.
[0042] Figure 4 It is a schematic diagram of frequency doubling test, wherein 1 is a laser, 2 is an incident laser beam, 3 is the Zn4(BO3)2(CO2CH2NH2)2·H2O crystal of Example 2, 4 is the generated outgoing laser beam, and 5 is a photomultiplier tube equipped with a filter.
[0043] Figure 5 This is the frequency doubling test result of the Zn4(BO3)2(CO2CH2NH2)2·H2O crystal sample in Example 2. DETAILED DESCRIPTION
[0044] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0045] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0046] Example 1 Preparation of Zn4(BO3)2(CO2CH2NH2)2·H2O Compound
[0047] Zn4(BO3)2(CO2CH2NH2)2·H2O crystals were prepared by the following steps:
[0048] (a) Zn(OH)2 (0.005 mol, 0.497 g), H3BO3 (0.01 mol, 0.618 g), C2H5NO2 (0.005 mol, 0.375 g), H2O (9 ml) and CF3COOH (0.5 ml) were placed in a reaction kettle with a polytetrafluoroethylene liner, and the temperature was increased to 180°C at a rate of 20°C / h and kept at this temperature for 2 days;
[0049] (b) After the reaction is completed, the system is cooled to room temperature at a rate of 5°C / h, and after separation and drying, Zn4(BO3)2(CO2CH2NH2)2·H2O compound can be obtained.
[0050] Example 2 Preparation of Zn4(BO3)2(CO2CH2NH2)2·H2O Crystals
[0051] Zn4(BO3)2(CO2CH2NH2)2·H2O crystals were prepared by the following steps:
[0052] (a) Zn(OH)2 (0.005 mol, 0.497 g), H3BO3 (0.01 mol, 0.618 g), C2H7ClNO2 (0.005 mol, 0.552 g), H2O (9 ml) and CF3COOH (0.5 ml) were placed in a reactor lined with polytetrafluoroethylene, heated to 180°C at a rate of 15°C / hour, and crystallized at this temperature for 5 days;
[0053] (b) After the crystallization is completed, the reaction system is cooled to room temperature at a rate of 5°C / h. After separation and drying, Zn4(BO3)2(CO2CH2NH2)2·H2O crystals can be obtained.
[0054] Example 3 Preparation of Zn4(BO3)2(CO2CH2NH2)2·H2O Crystals
[0055] Zn4(BO3)2(CO2CH2NH2)2·H2O crystals were prepared by the following steps:
[0056] (a) Zn(OH)2 (0.005 mol, 0.497 g), H3BO3 (0.01 mol, 0.618 g), C3H4N2O2 (0.005 mol, 0.5 g), H2O (5 ml) and CF3COOH (1 ml) were placed in a reactor with a polytetrafluoroethylene liner, and the temperature was raised to 180°C at a rate of 20°C / hour, and crystallized at the constant temperature for 5 days;
[0057] (b) After the crystallization is completed, the reaction system is cooled to room temperature at a rate of 5°C / h. After separation and drying, Zn4(BO3)2(CO2CH2NH2)2·H2O crystals can be obtained.
[0058] Example 4 Structural analysis of Zn4(BO3)2(CO2CH2NH2)2·H2O crystals
[0059] The single crystal X-ray diffraction and powder X-ray diffraction methods were used to analyze the structure of the Zn4(BO3)2(CO2CH2NH2)2·H2O crystal samples prepared in Examples 2-3. The single crystal X-ray diffraction was performed on an XtaLAB Pro MM003Cu / Mo single crystal X-ray diffractometer of Rigaku Corporation, Japan. The data collection temperature was 288.9K, and the diffraction light source was Cu-Kα radiation ( ), the scanning mode was ω=2θ, and the data were processed by Multi-Scan method for absorption correction. The structure analysis was completed by SHELXTL package; the position of heavy atoms was determined by direct method, and the coordinates of other atoms were obtained by difference Fourier synthesis method; the F-based 2 The full matrix least squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters. Among them, the single crystal X-ray diffraction results show that the chemical formula of the samples in Examples 2 to 3 is Zn4(BO3)2(CO2CH2NH2)2·H2O, belonging to the trigonal system, the space group is P3221, and the unit cell parameters are α=β=90°,γ=120°,z=6. The schematic diagram of the crystal structure is as follows Figure 1 shown.
[0060] Powder X-ray diffraction (XRD) data were collected using a Rigaku SmartLab 9kW diffractometer with a fixed target monochromatic light source of Cu-Kα and a wavelength of The scanning range is 5-70°, and the scanning step is 0.02°. The powder X-ray diffraction spectrum shows that the diffraction peak positions of the samples in Examples 1-3 are basically the same. Taking the sample in Example 2 as a typical representative, its powder X-ray diffraction spectrum results are as follows: Figure 2 The results in the figure show that the X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is basically consistent with the peak position and peak intensity of the powder X-ray diffraction pattern of the Zn4(BO3)2(CO2CH2NH2)2·H2O crystal sample prepared in Example 2.
[0061] Example 5 Frequency doubling test experiment of Zn4(BO3)2(CO2CH2NH2)2·H2O crystal
[0062] The Zn4(BO3)2(CO2CH2NH2)2·H2O crystal sample prepared in Example 2 was subjected to a frequency doubling test experiment. The 1064nm laser emitted by a Nd:YAG solid laser was used as the fundamental frequency light to irradiate the Zn4(BO3)2(CO2CH2NH2)2·H2O crystal powder prepared in Example 2. The generated frequency doubling light was detected by a photomultiplier tube, and the harmonic intensity was displayed by an oscilloscope. The specific method is as follows:
[0063] The particle sizes of the crystal samples to be tested are sieved into 45-60 μm, 60-70 μm, 70-100 μm, 100-150 μm, 150-200 μm, 200-250 μm, 250-325 μm and 325-500 μm using a standard sieve, and the crystal samples to be tested with the above particle sizes are placed on Figure 4 At position 3 in the device shown, at room temperature, a Q-switched Nd:YAG laser is used as the input light source (i.e., laser 1), and the incident wavelength of the incident laser beam 2 is 1064nm. After the incident laser beam 2 passes through the crystal 3 of Example 2, the frequency-doubled signal of the outgoing laser beam 4 after passing through the filter 5 is tested respectively, and the variation trend of the frequency-doubled signal with the particle size is observed to determine whether phase matching can be achieved. Under the same test conditions, KH2PO4 (KDP) is used as the reference for the double frequency test. The test results are shown in FIG. Figure 5 As shown, Figure 5 The results show that the powder frequency-doubled effect of Zn4(BO3)2(CO2CH2NH2)2·H2O crystal under 1064nm laser irradiation is about 0.85 times that of KDP under the same conditions, and phase matching can be achieved.
[0064] Example 6 Spectral Performance Test of Zn4(BO3)2(CO2CH2NH2)2·H2O Crystal
[0065] The Zn4(BO3)2(CO2CH2NH2)2·H2O crystal sample prepared in Example 2 was used as a representative to conduct spectral performance tests from ultraviolet to near-infrared.
[0066] UV-Vis-NIR transmission spectrum test was performed on Hitachi UV-Vis-NIR spectrophotometer (Japan). The test results are shown in Figure 3 As shown, Figure 3 The results show that Zn4(BO3)2(CO2CH2NH2)2·H2O crystal has a wide transmittance range and a high transmittance in the spectral range of 240-1400nm. The ultraviolet absorption cutoff wavelength can reach 201nm. By conversion, it can be known that its band gap is 6.17eV.
[0067] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A compound, characterized in that Its chemical formula is Zn4(BO3)2(CO2CH2NH2)2·H2O.
2. The method for preparing the compound according to claim 1, characterized in that: The method comprises the following steps: The compound containing Zn, the compound containing B and the compound containing glycine ligand are mixed and subjected to hydrothermal reaction to prepare the compound.
3. The method according to claim 2, characterized in that The Zn-containing compound is selected from at least one of ZnO, Zn(OH)2, and ZnC4H8N2O4. Preferably, the B-containing compound is selected from at least one of H3BO3, B2O3, and HBO2. Preferably, the glycine-containing ligand compound is selected from one of C3H4N2O2, C2H5NO2, and C2H7ClNO2. Preferably, the molar ratio of the Zn-containing compound, the B-containing compound and the glycine ligand-containing compound is (1-3):(1-3):
1.
4. The method according to claim 2, characterized in that: The hydrothermal reaction is carried out in a solvent, and the solvent is selected from a mixed solvent of water and CF3COOH; Preferably, the reaction temperature of the hydrothermal reaction is 160-200° C.; and the reaction time of the hydrothermal reaction is 1-5 days.
5. A nonlinear optical crystal, characterized in that: The chemical formula of the crystal is Zn4(BO3)2(CO2CH2NH2)2·H2O as described in claim 1, that is, the nonlinear optical crystal is Zn4(BO3)2(CO2CH2NH2)2·H2O crystal.
6. The crystal according to claim 5, characterized in that The Zn4(BO3)2(CO2CH2NH2)2·H2O crystal belongs to the trigonal system, the space group is P3221, and the unit cell parameters are α=β=90°, γ=120°, z=6.
7. The crystal according to claim 5, characterized in that The Zn4(BO3)2(CO2CH2NH2)2·H2O crystal structure consists of a honeycomb [Zn2BO3ON] ∞ Layers and glycine organic layers are stacked alternately.
8. The method for preparing the crystal according to any one of claims 5 to 7, characterized in that: The method comprises: mixing a Zn-containing compound, a B-containing compound, a glycine ligand-containing compound and a solvent, and heating and crystallizing the mixture to obtain the crystal.
9. The method according to claim 8, characterized in that The heating crystallization temperature is 160-200°C; The heating crystallization time is 3 to 10 days.
10. The crystal according to any one of claims 5 to 7 is used in the fields of laser frequency doubling, electro-optic modulation, photorefractive information processing and information storage or catalysis; preferably, it is used as a frequency doubling device in an all-solid-state laser.
Citation Information
Patent Citations
Zn-Tb coordination polymer luminescent material based on like-amino acid ligand and preparation method thereof
CN103012501A
Method for preparing porous zinc oxide with three-dimensional structure
CN105565366A
Preparation method and crystal form of substituted borate compound
CN109251218A
Infrared non-linear optical crystal, preparation process and application thereof
US20180259827A1